Angle and time of arrival statistics for circular and elliptical scattering models. - Ertel, R.B (IEEE Journal on selected areas in communications)
With the introduction of antenna array systems into wireless communication networks comes the need to better understand the spatial characteristics of the channel. Scattering models provide both angle of arrival (AOA) and time of arrival (TOA) statistics of the channel. A number of different scattering models have been proposed in the literature including elliptical and circular models. These models assume that scatterers lie within an elliptical and circular region in space, respectively. In this paper, the joint TOA/AOA, the marginal TOA, and the marginal AOA probability density functions (PDFs) are derived for the elliptical and circular scattering models. These PDFs provide insight into the properties of the spatial wireless channel